Emergency Percutaneous Pulmonary Valve Implantation in a Tetralogy of Fallot Patient With Refractory Cardiogenic Shock - Simon Anquetil, MD; Grégoire Albenque, MD, MSc; Clément Batteux, MD; Nicolas Combes, MD; Stefano Bartoletti, MD; Saïd Bichali, MD; Ali Houeijeh, MD, PhD; Sébastien Hascoët, MD, PhD (JACC: Case Reports, 2025)
Background: Tetralogy of Fallot (TOF), the most common cyanogenic congenital heart disease at birth, often leads to later complications such as pulmonary regurgitation (PR), right ventricular failure, and atrial or ventricular arrhythmias after complete surgical repair. Percutaneous pulmonary valve implantation (PPVI) is an alternative to surgery to treat a right-ventricular outflow tract dysfunction. Case Summary: We present here an atypical case of an emergency PPVI in a 69-year-old TOF patient in refractory cardiogenic shock with severe PR decompensated by new-onset rapid atrial fibrillation. Discussion: Recent data show that PPVI is usually carried out on an elective basis, with procedures rarely performed in emergencies.